Optimization of Ergonomic and User-Safe Organic Waste Shredding Machine Design Using Quality Function Deployment (QFD) - Rimantho, Dino (P3M Politeknik Perkapalan Negeri Surabaya, 2025)
The increasing volume of waste in Indonesia, especially from households and traditional markets, necessitates innovative technological solutions for effective waste management. This study presents the development of an ergonomic organic waste shredding machine prototype, designed with a focus on safety and ease of use. By applying the Quality Function Deployment (QFD) method, user needs were translated into technical specifications using the House of Quality (HoQ). Primary data was collected through questionnaires, while anthropometric and design data were used to ensure ergonomic suitability. The results indicate that key user priorities include ease of cleaning, minimal noise, and ergonomic height. The design phase includes material selection, component acquisition, and prototype modeling. This innovation supports SDG 11: sustainable cities and communities, and SDG 12 responsible consumption and production